A protein-mRNA feedback exists in miR-21-associated E-selectin expression. (1st May 2019) - Tang, Siyuan; Liu, Bailong; Liu, Jiaqi; Wang, Jian; Wang, Ya
Abstract: Purpose: To study whether miR-21, an oncogene associated with lung tumorigenesis, affects immune response. Material and methods: Cancer immune-related 786 mRNA expression was compared in lung tissue from wild- type and miR-21 knock-in mice using NanoString technology. The significantly changed genes were verified using real-time PCR. E-Selectin (Sele) was subsequently identified for further examination using immunohistochemistry (IHC) and Western blot in the same lung tissue. The mouse Sele 3'untranslated region (3'-UTR) was searched to identify a miR-21 matching sequence. The Sele level in miR-21 mimic transfected mouse lung bronchial epithelial (LBE) cells was examined. Results: We unexpectedly found that the Sele mRNA level significantly increased but the protein level significantly decreased in the lung tissue of miR-21 knock-in mice compared to the mRNA/protein levels in the lung tissue of wild- type mice. The mouse Sele 3'-UTR contains the key sequence that can be targeted by miR-21. The Sele levels decreased in mouse LBE cells after miR-21 mimic transfection. Conclusion: Sele is a potential miR-21 target. The opposing Sele levels at mRNA and protein suggest a feedback-regulation from protein to mRNA. The feedback-regulation in miR-21-suppressed gene expression indicates that we should carefully evaluate any data from mRNA array since they may not reflect real protein expression status.